A Framework for Multiobjective Decision Management with Diverse Stakeholders. Issue 4 (21st August 2017) - Garber, Melissa; Sarkani, Shahram; Mazzuchi, Thomas
ABSTRACT: Today's society faces increasingly "Big Decisions, " including those related to strategy, policy, and system of systems lifecycle design. As corporate and governmental "Big Decisions" increase in complexity over time, they affect larger numbers, and more diverse groups, of stakeholders. This paper proposes a framework for decision making, based on the INCOSE Decision Management Process, that adds the perspectives of multiple stakeholder views. Using this framework, the views of diverse stakeholder groups, such as senior leaders, users, competitors, suppliers, civic organizations, and environmental organizations, are combined to facilitate stakeholder‐centric perspectives on tradeoffs. The Group Decision Analysis Theorem is applied to combine stakeholder perspectives. Visualizations are utilized to improve stakeholder understanding, clarify relationships, and provide views into tradeoffs. The framework is demonstrated through an example based on space exploration policy.